Factors associated with self-reported exposure to chemical substances at work in Brazil: results from the National Health Survey, 2013 - Ada Ávila Assunção; Mery Natali Silva Abreu; Priscila Sílvia Nunes Souza (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To describe the prevalence of self-reported exposure to chemical substances at work and its associated factors in a sample of Brazilian adults that participated in the National Health Survey, conducted between 2013 and 2014. METHODS Our sample consisted of adults aged 18 years or older that answered question E1 of module E: "In the week of July 21-27, 2013 (reference week), did you work as regular employee or intern for at least an hour in any activity paid with cash?" Sociodemographic data, situation and health behaviors were analyzed with single and multivariate binary logistic regression. The model was adjusted by the variables of all groups, adopting a 5% significance level. The values of odds ratio (OR) and respective confidence intervals were obtained. RESULTS Women (OR = 0.74; 95%CI 0.66-0.82) had a lower chance of exposure to chemicals. The highest chances were observed in groups with no instruction or that attended up to middle-school (OR = 1.77; 95%CI 1.50-2.08), high school (OR = 1.62; 95%CI 1.37-1.91), age between 25 and 54 years (OR = 1.26; 95%CI 1.07-1.48), current smokers (OR = 1.21; 95%CI 1.07-1.37), who reported tiredness (OR = 1.35; 95%CI 1.21-1.50), hearing difficulties (OR = 1.24; 95%CI 1.04-1.48) and who reported having suffered an accident at work (OR = 2.00; 95%CI 1.57-2.54). CONCLUSIONS The unprecedented results cover the entire workforce. Positive associations with hearing loss, smoking and history of work accidents are consistent, as well as the inverse association with education level and gender differences. The absence of association with asthma was surprising. To fill gaps in investigations on chronic non-communicable diseases, we suggested improving the PNS collection instrument in the occupational dimension.